miRNA-Dependent CD4+ T Cell Differentiation in the Pathogenesis of Multiple Sclerosis - Basak, Justyna; Majsterek, Ireneusz (Multiple sclerosis international, 2021)
Multiple sclerosis (MS) is characterized by multifocal lesions, chronic inflammatory condition, and degenerative processes within the central nervous system (CNS) leading to demyelination. The most important cells involved in its pathogenesis are those which are CD4+, particularly proinflammatory Th1/Th17 and regulatory Treg. Signal cascades associated with CD4+ differentiation are regulated by microRNAs (miRNAs): short, single-stranded RNAs, responsible for negative regulation of gene expression at the posttranscriptional level. Several miRNAs have been consistently reported as showing dysregulated expression in MS, and their expression patterns may be elevated or decreased, depending on the function of specific miRNA in the immune system. Studies in MS patients indicate that, among others, miR-141, miR-200a, miR-155, miR-223, and miR-326 are upregulated, while miR-15b, miR-20b, miR-26a, and miR-30a are downregulated. Dysregulation of these miRNAs may contribute to the imbalance between pro- and anti-inflammatory processes, since their targets are associated with the regulation of Th1/Th17 and Treg cell differentiation. Highly expressed miRNAs can in turn suppress translation of key Th1/Th17 differentiation inhibitors. miRNA dysregulation may result from the impact of various factors at each stage of their biogenesis. Immature miRNA undergoes multistage transcriptional and posttranscriptional modifications; therefore, any protein involved in the processing of miRNAs can potentially lead to disturbances in their expression. Epigenetic modifications that have a direct impact on miRNA gene transcription may also play an important role.